Early symbiotic rugosan endobionts in stromatoporoids from the Rhuddanian of Estonia (Baltica). (14th October 2016) - Vinn, Olev; Toom, Ursula
Abstract : The earliest known symbiotic rugosan endobionts occur in stromatoporoids from the early Rhuddanian of Estonia. The stromatoporoid Ecclimadictyon nikitini from the Tamsalu Formation contains the rugosan Donacophyllum middendorffii endobiont. A stromatoporoid Clathrodictyon boreale from the Varbola Formation contains Streptelasma estonica and Bodophyllum sp. endobionts. There are up to three endobiotic rugosans per stromatoporoid host. Stromatoporoid hosts were beneficial for symbiotic rugosans as elevated substrates on a seafloor that offered a higher tier for feeding; they also offered enhanced substrate stability. Stromatoporoids of the end‐Ordovician mass‐extinction recovery fauna hosted a diverse fauna of symbiotic endobionts. There were few if any negative effects of this mass extinction on the symbiotic endobionts.